Phytoseiidae (Acari: Mesostigmata) from rubber tree crops in the State of Bahia, Brazil, with description of two new species - Nuvoloni, Felipe Micali; Lofego, Antonio Carlos; Castro, Elizeu Barbosa; Feres, Reinaldo José Fazzio (Zootaxa, 2015)
The current study describes the results of a survey of Phytoseiidae mites conducted on a rubber tree plantation in the State of Bahia, Brazil. We present 22 species, two of which are new to science, Amblydromalus insolitus n. sp. Nuvoloni & Lofego, and Typhlodromips paramilus n. sp. Nuvoloni & Lofego, and three new records for this host are presented. The species composition was more related with the records of the northern Brazilian Region, than with that of Southeastern and Midwestern.